Effectiveness of Promotion at Bebek Ria Padang Restaurant - putri mayang sari; Lise Asnur (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
This research is motivated by the ups and downs of the number of visitors who come to the Duck Ria Padang restaurant due to less-than-optimal promotions. The purpose of this study was to determine the effectiveness of promotion at the Duck Ria Padang restaurant and to describe the effectiveness of the promotion at the Ria Padang Restaurant in terms of the five elements in the promotion mix (advertising, sales promotion, personal selling, direct marketing, and public relations). This type of research is descriptive with qualitative data. Sampling using a purposive sampling technique. There were 5 informants from this study, including 1 owner of the Duck Ria Padang restaurant, 2 employees of the Duck Ria Padang restaurant, and 2 guests who were visiting the Duck Ria Padang restaurant. The results showed that: 1) advertising carried out such as Instagram and Facebook was not actively carried out by the owner, 2) the price offered by Duck Ria Padang did not match the menu provided by the Duck Ria Padang restaurant, 3) the personal sales indicator of the offer. directly carried out by waiters and waitresses at the Duck Ria Padang restaurant to guests who were visiting were carried out in a good and detailed manner, 4) direct marketing of mail orders was less active by the Duck Ria Padang restaurant because employees often got mistakes every guest who ordered in the mail order (go food), 5) public relations at the Duck Ria Padang restaurant is very good as seen on google reviews.